HUBUNGAN SPIRITUALITAS DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL TERMINAL (GGT) YANG MENJALANI HEMODIALISIS DI RSUD KABUPATEN BULELENG - Septiani, Rika; Antari, Gusti Ayu Ary; Kamayani, Made Oka Ari (Coping: Community of Publishing in Nursing; Vol 9 No 3 (2021): Juni 2021DO - 10.24843/coping.2021.v09.i03.p04, 2021)
Patients with kidney failure must receive replacement therapy for kidney function; one of them is hemodialysis. Long-term hemodialysis therapy causes changes in aspects of life; one of them is psychological changes that give rise to response to spiritual expressions in the form of negative or positive responses. Negative response will have an impact on the quality of life patients. This study aimed to determine whether there was a relationship between spirituality and the life quality of kidney failure patients that underwent hemodialysis in RSUD Buleleng. This research is a descriptive correlational study with a cross-sectional design and purposive sampling technique. The amount of sample in this study was 92 patients who underwent hemodialysis in RSUD Buleleng. The Spearman Rank test results on spirituality and quality of life variables obtained p-value 0.001 (p <0.05), which means there was a moderate positive relationship between spirituality and quality of life kidney failure patients that underwent hemodialysis in RSUD Buleleng. So it can be concluded that if spirituality is high, the quality of life will be okay. Suggested for hemodialysis nurses can implement holistic treatments expecially to improve aspects of spirituality so that they can maintain the life quality of patients that undergoes hemodialysis.